1996
DOI: 10.2307/3870215
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Induces Mitogen-Activated Protein Kinase Activation in Barley Aleurone Protoplasts

Abstract: Abscisic acid (ABA) induces a rapid and transient mitogen-activated protein (MAP) kinase activation in barley aleurone protoplasts. MAP kinase activity, measured as myelin basic protein phosphorylation by MAP kinase immunoprecipitates, increased after 1 min, peaked after 3 min, and decreased to basal levels after ~5 min of ABA treatment in vivo. Antibodies recognizing phosphorylated tyrosine residues precipitate with myelin basic protein kinase activity that has identical ABA activation characteristics and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 34 publications
8
127
0
2
Order By: Relevance
“…These results indicate that a protein phosphorylation and dephosphorylation process might be involved in ABAresponsive signaling during water deficit. Recently, ABA was shown to induce a rapid and transient activation of MAPK in barley aleurone protoplasts (Knetsch et al, 1996). Correlation between ABA-induced MAPK activation and ABA-induced gene expression implies that MAPK might be involved in ABA signal transduction (Fig.…”
Section: Aba Signal Transductionmentioning
confidence: 99%
“…These results indicate that a protein phosphorylation and dephosphorylation process might be involved in ABAresponsive signaling during water deficit. Recently, ABA was shown to induce a rapid and transient activation of MAPK in barley aleurone protoplasts (Knetsch et al, 1996). Correlation between ABA-induced MAPK activation and ABA-induced gene expression implies that MAPK might be involved in ABA signal transduction (Fig.…”
Section: Aba Signal Transductionmentioning
confidence: 99%
“…The "early" genes include those encoding members of a MAPK cascade, some of which are induced within 1-10 min of stress or ABA treatment, as well as transcription factors and early response to dehydration (erd) genes (reviewed in Shinozaki and Yamaguchi-Shinozaki, 2000;Xiong and Zhu, 2001). It is noteworthy that many of the genes encoding presumed signaling components show relatively specific induction by drought, cold, salinity, wounding or osmotic stress, but only one of these has been shown to be ABA-responsive (Knetsch et al, 1996). Similarly although ABA signaling can be mediated by inositol 1,4,5-triphosphate, hyperosmotic stress induces a rapid and transient increase in IP 3 independent of abscisic acid in Arabidopsis cell culture (Takahashi et al, 2001).…”
Section: Stress Responsesmentioning
confidence: 99%
“…ABA was shown to induce MAPK activation in barley aleurone layers (14), and a possible MAPK activity was observed in Vicia guard cell protoplasts (15). Furthermore, a study with pea epidermal peels showed that the MAPKK inhibitor PD98059 inhibits ABA-induced stomatal closure and expression of an ABA-inducible dehydrin gene (16,17).…”
mentioning
confidence: 99%